Advances in Catalytic Oxidation of Volatile Organic Compounds over Pd-Supported Catalysts: Recent Trends and Challenges - Shengnan Song (Frontiers in Materials, 2020)
Volatile organic compounds (VOCs) are poisonous and regarded as the paramount source for the formation of secondary organic aerosols, ozone, and photochemical smog, greatly affecting human health and environment quality. In order to abate VOC emission, catalytic oxidation is widely applied in industries and is believed to be an efficient and economically feasible way for the elimination of VOCs. This review is primarily concentrated on summarizing the recent progress and developments in the catalytic oxidation of various VOCs over Pd-supported catalysts. Despite their high catalytic performances at much lower temperatures, the wide use of Pd-supported catalysts in the industry has been limited by their high cost, low thermal stability, and incomplete oxidation of VOCs. Hence, the intrinsic properties of the active sites and supports, the reaction conditions, the deactivation mechanism, and the strategy to reveal the catalytic oxidation pathway are also systematically summarized. This review aims to give a deep comprehension and guidance for the development of efficient and cost-effective Pd-supported catalysts in the near future.